Synthesis, cytotoxicity and dna binding studies of ruthenium(ii) mixed-polypyridyl complexes - Harun, Siti Norain (2015)
A series of ruthenium(II) complexes, including two novel compounds [Ru(dppz)2L]2+ where dppz = dipyrido-[3,2-a:2’,3’-c]phenazine, and L = 2-phenylimidazo[4,5- f][1,10]phenanthroline (PIP) or 2-(4-hydroxyphenyl)imidazo[4,5-f][1,10] phenanthroline (p-HPIP) have been synthesized and characterized. The previously reported complexes [Ru(bpy)2L]2+ and [Ru(phen)2L]2+ were also prepared. All complexes were characterized by elemental analysis, 1H-NMR spectroscopy, ESI-Mass spectroscopy and FT-IR spectroscopy. The photophysical properties were analyzed by UV-Visible spectroscopy and fluorescence spectroscopy. [Ru(dppz)2PIP]2+ and [Ru(dppz)2p-HPIP]2+ displayed ‘molecular light-switch’ effect as they have high emission in acetonitrile but no emission in water. The cytotoxicity of all complexes against cancer cell lines Hela and MCF-7 were investigated through standard MTT assay. [Ru(dppz)2PIP]2+ showed moderate toxicity on both MCF-7 and Hela with IC50 of 37.64 µM and 28.02 µM, respectively. Interestingly, [Ru(dppz)2p-HPIP]2+ exhibited remarkable cytotoxicity results with IC50 of 13.52 µM on Hela and 11.63 µM on MCF- 7 cell lines which are comparable to the infamous anti-cancer drug, cisplatin. The cytotoxixity of this complex series increased as the ligands size extended in order of [Ru(bpy)2L]2+ < [Ru(phen)2L]2+ < [Ru(dppz)2L]2+. The interaction of both new complexes [Ru(dppz)2PIP]2+ and [Ru(dppz)2p-HPIP]2+ with CT-DNA were explored by using UV-Vis absorption titration, fluorescence quenching and viscosity measurement. These studies suggest that the two Ru(II) complexes bind to DNA via intercalation, which involves the insertion of ligands in between DNA base pairs. The absorption titration determined that, [Ru(dppz)2p-HPIP]2+ (Kb = 5.0 x 107 M-1) bind strongly to DNA strongly than [Ru(dppz)2PIP]2+ (Kb = 2.5 x 106 M-1). The intramolecular hydrogen bonding in HPIP complex increases the surface area of the intercalating diimines and enhances the DNA binding affinity substantially.